Airway function in healthy and chronic respiratory diseased. An observational cohort study in Rwanda - Musafiri, Sanctus (Afrika Focus, 2012)
This is the rst study which shows the prevalence of atopy, asthma and COPD in Rwanda. Asthma and COPD were respectively diagnosed in 8.9% and 4.5% of the participants. COPD was diagnosed in 9.6% of the subjects aged ≥ 45 years and was higher among current smokers (11.2%). Spirometric reference values in our study were nearly similar to those for black Americans by Hankinson. Considering the similarities of the Great Lake regions inhabitants, the reference equations obtained in Rwanda population can be used in neighbouring countries while waiting for further studies in the region.